Two Early Quaker Pamphlets from the East of England - McArthur, Euan David (Quaker studies, 2024)
This research note contextualises, and in one case transcribes, two early pamphlets concerning the Quakers which remain difficult to access. In each, dated 1655 and 1659, we can see crucial early interactions between the movement and outsiders.The earlier, an anti-Quaker work, details a sexual scandal in Norfolk that brought criticism from within and without the movement, including local magistrates and an active puritan community. Though compiled by a critic, the text includes written testimonies by Quakers. The later text concerns a series of disputes at the University of Cambridge, illustrating the development of debating styles between Quakers and scholars, as well as the occasional dislocation between in-person disputes and their transcription. In both cases, Friends set about drawing early dividing lines, in a region of Britain which has often received less scholarly attention.